Flipping a mathematics course, a blended learning approach - Lopes, Ana Paula (2018)
Flipped classroom pedagogy has become popular in several different courses in Higher Educational Institutions (HEI). Important advantages being the increased level of lecturer and student interaction, which can have a strong impact on students’ motivation, engagement, satisfaction and performance. A flipped based experiment was implemented in 2015-2016 and 2016-2017 in a Mathematics Course, at the Institute of Accounting and Administration of Porto (ISCAP), using Moodle quizzes reinforced by in-class activities and support via PowerPoint with audio support, YouTube tutorial videos and online reading materials before and after classes. In this new organizational design for the teaching and learning paradigm, as its name transmits, there was pedagogical switch of the traditional academic procedure as students’ first contact with the subjects and themes was made outside the “four wall classroom bounds”. Teachers’ role was transposed into a kind of guide and facilitator, indicating the way to go, avoiding to walk in a parallel path, or even ahead, but indicating the way to go, motivating students in their own knowledge construction, letting them lead the way, following and supporting, constantly and carefully monitoring their learning outcomes, only interfering in the learning process as an anchor where students can rely, adjusting the right paths when they seem to deviate from the predefined learning goals. Classroom time was consumed with open discussions, solving tasks and application problems, clarifying the supporting fundaments, in order to improve students’ engagement into their learning process in a collaborative environment. The operational stages and procedures will be described and, additionally, several results obtained during its implementation will be presented.